Spin-reorientation phase transitions in soft magnetic films of different anisotropy - Bezus, A.V.; Mamalui, Yu.A.; Siryuk, Yu.A. (Functional Materials, 2008)
The spin-reorientation phase transitions (SRPT) in thin magnetic ferrite-garnet films of mixed anisotropy have been studied. In a film with strong uniaxial anisotropy, a first order SRPT from axial to angular phase occurs, the new angular phase being nucleated from the old domain boundary. In a low anisotropy film, the nucleation occurs from one angular phase to another with no boundary between new and old phases, no nuclei being formed by domain magnetization vector rotation to a more energetically favorable state. The SRPT in bilayer film with TK in one of layers takes place due to combined action of rare-earth sublattice magnetization and bias-field of another layer. Досліджено спін-переорієнтовані фазові переходи (СПФП) у тонких плівках феритівгранатів зі змішаною анізотропією. У плівці з сильною одновісною анізотропією відбувається СПФП першого роду від вісьової до кутової фази з зародкоутворенням нової фази із старої доменної межі. Ріст зародків відбувається без утворення межі між новою та старою фазами. У плівці з малою анізотропією СПФП відбувається із кутової фази в другу кутову фазу без утворення зародків шляхом повороту вектора намагніченості у енергетично більш вигідний тан. У двошаровій плівці, що має в одному з шарів ТК, спостерігається СПФП внаслідок сумарної дії намагніченості рідкісноземельної підгратки та підмагнічуючого поля другого шару. Исследованы спин-переориентационные фазовые переходы (СПФП) в тонких магнитных пленках ферритов-гранатов со смешанной анизотропией. В пленке с сильной одноосной анизотропией происходит СПФП 1 рода от осевой к угловой фазе с зародышеобразованием новой фазы из старой доменной границы. Рост зародышей происходит из угловой фазы в другую угловую фазу без образования зародышей путем поворота вектора намагниченности в энергетически более выгодное состояние. В двуслойной пленке, имеющей в одном из слоев ТК, наблюдается СПФП вследствие суммарного действия намагниченности редкоземельной подрешетки и подмагничивающего поля другого слоя.